Evaluation of Polish Wild Mushrooms as Beta-Glucan Sources - Mirończuk-Chodakowska, Iwona (Int J Environ Res Public Health, 2020)
Mushroom beta-glucans show immunomodulatory, anticancer and antioxidant features. Numerous papers have been published in the last years on fungal polysaccharides, especially beta-glucans, demonstrating their various biological activities. However substantial data about beta-glucan contents in many mushroom species, especially wild mushrooms, are still missing. Therefore, the main objective of the study was to evaluate β-glucans in 18 species of wild mushrooms and three species of commercial mushrooms for comparison purposes. The contents of β-glucans were determined by the Megazyme method and with the Congo red method, which differ in analytical procedure. Among wild mushrooms, the highest mean β-glucan content assessed with the Megazyme method was found in Tricholoma portentosum (34.97 g/100 g DM), whereas with the Congo red method in Lactarius deliciosus (17.11 g/100 g DM) and Suillus grevillei (16.97 g/100 g DM). The β-glucans in wild mushrooms assessed with the Megazyme method were comparable to commercial mushrooms, whereas β-glucans assessed with the Congo red method were generally higher in wild mushrooms, especially in Russula vinosa, L. deliciosus and S. grevillei. This study indicates wild mushrooms as interesting material for β-glucan extraction for food industry and medicinal purposes.